A Review of Additive Manufacturing Techniques and Post-Processing for High-Temperature Titanium Alloys - Binquan Jin; Qing Wang; Lizhong Zhao; Anjian Pan; Xuefeng Ding; Wei Gao; Yufeng Song; Xuefeng Zhang (Metals, 2023)
Owing to excellent high-temperature mechanical properties, i.e., high heat resistance, high strength, and high corrosion resistance, Ti alloys can be widely used as structural components, such as blades and wafers, in aero-engines. Due to the complex shapes, however, it is difficult to fabricate these components via traditional casting or plastic forming. It has been proved that additive manufacturing (AM) is an effective method of manufacturing such complex components. In this study, four main additive manufacturing processes for Ti alloy components were reviewed, including laser powder bed melting (SLM), electron beam powder bed melting (EBM), wire arc additive manufacturing (WAAM), and cold spraying additive manufacturing (CSAM). Meanwhile, the technological process and mechanical properties at high temperature were summarized. It is proposed that the additive manufacturing of titanium alloys follows a progressive path comprising four key developmental stages and research directions: investigating printing mechanisms, optimizing process parameters, in situ addition of trace elements, and layered material design. It is crucial to consider the development stage of each specific additive manufacturing process in order to select appropriate research directions. Moreover, the corresponding post-treatment was also analyzed to tailor the microstructure and high-temperature mechanical properties of AMed Ti alloys. Thereafter, to improve the mechanical properties of the product, it is necessary to match the post-treatment method with an appropriate additive manufacturing process. The additive manufacturing and the following post-treatment are expected to gradually meet the high-temperature mechanical requirements of all kinds of high-temperature structural components of Ti alloys.